(untitled) (Journal of Plant Disease Sciences, 2025)
Soybean is one of the most economically important legumes worldwide. However, diseases serve as significant biotic constraints in soybean production. Among them, charcoal rot caused by Macrophomina phaseolina is a major disease responsible for substantial yield losses. In the present investigation, five fungicides and three bio-agents were evaluated for their efficacy against M. phaseolina. In in vitro conditions, Carboxin 37.5% + Thiram 37.5% DS and Carbendazim 12% + Mancozeb 63% WP exhibited 100% inhibition of the mycelial growth of the pathogen. Among the bio-agents tested, Trichoderma viride showed the highest mycelial growth inhibition (58.33%), followed by Pseudomonas fluorescens (38.88%). Under greenhouse conditions, Carboxin 37.5% + Thiram 37.5% DS and Carbendazim 12% + Mancozeb 63% WP were found to be the most effective, achieving 77.78% disease control of charcoal rot. This was followed by Thiophanate methyl 45% + Pyraclostrobin 5% FS (55.56%), Trichoderma viride (33.33%), and Pseudomonas fluorescens (22.22%).